Integrated Riparian Buffer Zones and Floating Treatment Wetlands for Mitigating Agricultural Nutrient Runoff in the Lerma–Chapala Basin, Mexico - Matilda Munoz; Carmen Pech Hernandez; Maria Sofia May (Program Pascasarjana Universitas Sriwijaya, 2026)
Background: Non-point source agricultural runoff is the dominant driver of eutrophication in the Lerma–Chapala Basin, central Mexico, yet field evidence on coupling terrestrial and aquatic nature-based solutions in a large degraded watershed remains scarce. Objective: To quantify the efficacy of riparian buffer zones (RBZ) and floating treatment wetlands (FTW), applied individually and combined, in attenuating total nitrogen (TN) and total phosphorus (TP). Methods: 120 sites (n=30 per treatment: Control, RBZ-Only, FTW-Only, Combined) were monitored bi-weekly over a full annual cycle; paired inlet–outlet TN and TP were determined by APHA spectrophotometric methods and compared using ANOVA with Tukey HSD, correlation, OLS regression, PCA and nutrient indices (Figure 1). Results: Influent averaged 18.52±3.2 mg L⁻¹ TN and 4.21±0.9 mg L⁻¹ TP. Control attenuation was negligible (5.1% TN, 5.0% TP); the Combined system was synergistic, reducing TN by 74.9% and TP by 81.7% (effluent 4.8 and 0.8 mg L⁻¹). Differences were highly significant (TN F=663.4; TP F=846.4; both p<0.001; η²>0.94), with treatment the dominant predictor of effluent TN (R²=0.83). Conclusions: Integrating RBZ with FTW offers a scalable, low-cost framework for restoring aquatic equilibrium in intensively farmed subtropical basins.